The Impact Of FDI On Conflict In Sub-Saharan Africa - Akomatey, R (University of Ghana, 2017)
This study primarily is aimed at evaluating the impact of FDI net inflows on conflict among countries in the SSA region using binary logistic regression technique. A panel data of 44 countries is analyzed over a sample period of 1990 to 2015 due to availability of data. Results from the study shows that FDI inflow significantly reduces the likelihood of conflict among countries in SSA. The outcome of the study also shows that variable such as democracy significantly reduces the likelihood of conflict negatively. However, variables such as natural resources, population, and unemployment significantly increase the likelihood of conflict. Ethnic fractionalization, GDP growth and education did not contribute significantly to determination conflict. Furthermore, the average FDI net inflows to SSA have relatively been on the increase right from the end of the cold war (beginning of the study period) to the year 2015. It is also evident that, the average FDI net inflow to all conflict countries put together exceeded the average FDI net inflow to all non-conflict countries put together. But, in comparing individual countries, countries classified as non-conflict received more FDI on average than countries plagued conflict. The study recommends that regulators together with policy makers should put strategic measures in place to aid continuous increases in the amount of FDI net inflow to SSA substantially in order to help mitigate conflict within the sub-region.
Keywords: net inflows; ethnic; conflict; population; resources; countries; growth and education